The efficacy of a brief motivational enhancement education program on CPAP adherence in OSA: a randomized controlled trial - Lai, Agnes Y K; Fong, Daniel Y T; Lam, Jamie C M; Weaver, Terri E; Ip, Mary S M (Chest, 2014)
Poor adherence to CPAP treatment in OSA adversely affects the effectiveness of this therapy. This randomized controlled trial (RCT) examined the efficacy of a brief motivational enhancement education program in improving adherence to CPAP treatment in subjects with OSA. Subjects with newly diagnosed OSA were recruited into this RCT. The control group received usual advice on the importance of CPAP therapy and its care. The intervention group received usual care plus a brief motivational enhancement education program directed at enhancing the subjects' knowledge, motivation, and self-efficacy to use CPAP through the use of a 25-min video, a 20-min patient-centered interview, and a 10-min telephone follow-up. Self-reported daytime sleepiness adherence-related cognitions and quality of life were assessed at 1 month and 3 months. CPAP usage data were downloaded at the completion of this 3-month study. One hundred subjects with OSA (mean ± SD, age 52 ± 10 years; Epworth Sleepiness Scales [ESS], 9 ± 5; median [interquartile range] apnea-hypopnea index, 29 [20, 53] events/h) prescribed CPAP treatment were recruited. The intervention group had better CPAP use (higher daily CPAP usage by 2 h/d [Cohen d = 1.33, P < .001], a fourfold increase in the number using CPAP for ≥ 70% of days with ≥ 4 h/d [P < .001]), and greater improvements in daytime sleepiness (ESS) by 2.2 units (P = .001) and treatment self-efficacy by 0.2 units (P = .012) compared with the control group. Subjects with OSA who received motivational enhancement education in addition to usual care were more likely to show better adherence to CPAP treatment, with greater improvements in treatment self-efficacy and daytime sleepiness. ClinicalTrials.gov; No.: NCT01173406; URL: www.clinicaltrials.gov.